THE FOUNDING OF CORRUPTION CONVICTS TO DEVELOP CIVIC DISPOSITION - Sunatra, Melisa, Cecep Darmawan, (Department of Civic Education, 2015)
The founding of corruption convicts is still be done by government eventhough their crimes caused nation loss. This research applied case study approach to qualitative research as a method. It took place in The 1st Class Penitentiary of Sukamiskin Bandung. The findings and discussions of this research showed that: Form and materials that was directed in fostering corruption convicts to develop civic disposition accordance with law about Correctional. The effectiveness of fostering could be seen in the alteration of behaviour, attitude and character, Government had commitment in commiting many efforts to handle corruption. Many obstacles in the process of fostering derived from the convicts themselves. The effort in facing the obstacles was establishing cooperations with some related parties.